Polish Underground Extracts, no. 5 (1986) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. An Interview with Jacek Kuroń: The Impase and Our Hopes[from: Wola, no. 7(173) (17 February 1986)]Jacek Kuroń, a well-known opposition activist, assesses the present situation of the opposition movement in Poland. He recognizes that Solidarity can be effective as a pressure group, especially on the local, factory level; but he believes that it would stand a better chance of bringing about change if a struggle were to take place within the Polish communist party or a new configuration in the international political arena to come about. Germany and the Polish Problem / by Karol Grodkowski[from: Tygodnik Mazowsze, no. 156 (30 January 1986)]The recent visit by Willy Brandt to Warsaw prompted animated discussions in the Polish underground. This article in the leading Solidarity publication examines the internal and international implications of Poland's relationship with West Germany The Eyes of All "Zeks" Are Turned Toward Poland: An Interview with Natalia Gorbanevska[from: Tygodnik Mazowsze, no. 146 (14 November 1985)]In this Interview with a known Soviet dissident, the Warsaw Solidarity weekly is told of the differences between the work and treatment of the opposition in Poland and in the Soviet Union. The Opposition in Hungary: An Interview with Gabor Demszky[from: Tygodnik Mazowsze, no. 155 (23 January 1986)]Gabor Demszky is director of the unofficial Hungarian publishing house AB.